An Islamic view of human development: special reference to Abdul Rahman Ibn Khaldun - Machouche, Salah; Bensaid, Benaouda (IISTE, 2014)
A perusal of theories of human development reveals attempts to build a broad platform for growth characterized by an inclusive approach to the religious, historical and cultural diversity of world communities today. A poor representation of the theological tenets and ethical values underlying the perception and undertaking of human development unfortunately persists. This research examines the religious and moral perspective of Islam on human development while exploring the concept and structure of human development and its theological and ‘umranic implications in the framework of Islam. Of particular interest is the perspective of Ibn Khaldun (d. 1406), a Fourteenth-Century Muslim jurist, sociologist and economist who, in his Muqaddimah, dedicates serious discussion to a number of relevant themes including the innate nature of man, and development of human knowledge, skills and craft. His thesis highlights vision of catalyzing sustainable human development set according to fundamental Islamic themes such as stewardship, support and cooperation, defence, protective order or social organization, and the power of thinking. Ibn Khaldun’s perspective also provides some of the crucial keys necessary to understanding the value of human development according to the Islamic worldview while enriching contemporary scholarship with critical insights required for an effective approach to human development in a cross-cultural and multi-religious context. The understanding of the Islamic perspective on the issue of human development is instrumental not only to researchers in social sciences in general and Khaldunian studies in specific, but also to the ongoing discourse on human development in current times, and to topics such as economic productivity, efficiency and management of human resources. Keywords: Ibn Khaldun. Human development. Muqaddimah.